PV Microinverters: Latest Efficiency Rankings, Energy Yield Assessments, Firmware Issues - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

Microinverter testing update using high power modules: Efficiency, yield, and conformity to a new ”estimation formula” for variation of PV panel size - Krauter, Stefan; Bendfeld, Jörg; Möller, Marius Claus (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
The market for microinverters is growing, especially in Europe. Driven by the strongly rising prices for electricity, many small photovoltaic energy systems are being installed. Since monitoring for these plants is often quite costly, their yields are often not logged. Since 2014, microinverters have been studied at the University of Paderborn. The investigations are divided into indoor and outdoor tests. In the indoor area conversion efficiencies as a function of load have been measured with high accuracy and ranked according to Euro- and CEC weightings. In the outdoor laboratory, the behavior in the real world is tested. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules. Here, the investigations were carried out with modules of the power of 215 Wp until the year 2020. Because of the increasing module power nowadays, modules with an output of 360 Wp are now being used. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation resulting in the actual yield, any module & inverter configuration can be characterized by just the two coefficients.

Microinverter PV Systems: New Efficiency Rankings and Formula for Energy Yield Assessment for any PV Panel Size at different Microinverter types - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 8th World Conference on Photovoltaik Energy Conversion)

Module-Inverters (Microinverters): Influence of Module Size on Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EU PVSEC 2021))
Efficiencies and energy yields of microinverters available on the market during 2014‒2021 have been measured, compared, and ranked. Conversion efficiencies as a function of load have been measured indoors with high accuracy and ranked according to Euro- and CEC weightings. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules of 215 Wp (until 2020) and 360 Wp (starting 2021). Inverters with two inputs have been fed by two of those modules. DC input, AC power output and energy yield of each microinverter have been recorded by individual calibrated electricity meters. CEC and EU efficiency rankings have been computed and compared. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation y = ax + b resulting in the actual yield, any module & inverter configuration can be characterized by just the coefficients a and b.
Keywords: AC-modules; Microinverter; Power Conditioning; Efficiency; Yield; PV module size; saturation; performance

Micro-Inverters: An Update of Comparison of Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the EUPVSEC 2020)
Efficiencies and energy yields of microinverters available on the market during 2014‒2020 have been measured, compared, and ranked. Conversion efficiencies as a function of load have been measured indoors with high accuracy and ranked according to Euro- and CEC weightings. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules of 215 Wp each. Inverters with two inputs have been fed by two of those modules. DC input, AC power output and energy yield of each micro-inverter have been recorded by individual calibrated electricity meters. Apparently, some inverters have been optimized for high irradiance levels and ranked better at the CEC efficiency ranking, others performed very well also at low irradiance levels, thus ranking higher at in the EU efficiency ranking. Efficiency ranks are slightly deviating from rankings by energy yield measurements. At one inverter, a slow MPPT algorithm that barely could follow quickly changing irradiance levels is most probably responsible for this effect. Another inverter switched off for a while after operation at high power, another one failed permanently. Apparently, some inverters are been optimized to show excellent datasheet ratings for EU- or CEC- efficiency. On the other hand, two inverters (each featuring two inputs) did not show an outstanding performance at the EU- and CEC-ratings but achieved leading ranks for AC energy yields. For the customer, AC yield is a major performance indicator of a microinverter and should be included in the datasheet.

Einfluss der Betriebstemperatur auf den Wirkungsgrad von Modul-Wechselrichtern für PV-Netzeinspeisungen - Krauter, Stefan; Bendfeld, Jörg (Tagungsband des 35. Symposiums für Photovoltaische Solarenergie, Kloster Banz, Bad Staffelstein (Deutschland))

Elevated Temperatures Affecting Efficiency, Overall Performance and Energy Yield of PV Microinverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the EU PVSEC 2020)
During comparative measurements of different PV microinverters, two yield issues came up that could not be explored via conventional efficiency measurements, but do have a significant impact on electrical energy yield: First category of issues are either sluggish or nervously acting maximum–power–point–tracking devices, which lead to reduced energy yields. The other category of issues is thermal: As a first explanation for observed reduced energy yields, it has been assumed that the conversion efficiency degrades at higher operating temperatures. This matter has been investigated in this article: A change in conversion efficiency could not be observed for elevated operation temperatures up to 50°C, despite high-precision and repeated measurements. But it was found that some inverters temporarily interrupted (or entirely stopped) operation after long periods of running at high temperatures. Also, a reduction in potential maximum power output has been detected for those inverters. Summarizing: With a high degree of certainty it can be stated that those reported yield losses have been caused by the temporary shutdowns and power limitations of the inverters.
Keywords: AC-modules; Microinverter; Power Conditioning; Thermal Performance; Ventilation; Stability; Efficiency; Yield

Comparison of Microinverters: Update on Rankings of Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) JUNE 15 - AUGUST 21, 2020 VIRTUAL MEETING)
To compare efficiency and yield of many micro-inverters available on the world market in 2014-2020, an in- and outdoor test laboratory at the University of Paderborn has been set up. The inverters have been fed by identical and calibrated crystalline silicon PV modules of 215 Wp. To monitor accurately DC input, AC power output and energy yield, each of the micro-inverters has been equipped with a calibrated electricity meter. For micro-inverters requiring control units for grid-feeding that has been acquired also. The comparison covers efficiency-load characteristics as well as electrical energy yields. Purchase costs vary considerably between the models in comparison, sometimes inverter costs are higher than module costs, particularly if an additional grid-connection or interface device is needed for operation. The weighted conversion efficiency according to EU and CEC standards has been measured and calculated. While some inverters have been optimized for high irradiance levels, they ranked better at the CEC efficiency, others performed very well also for low irradiance levels, thus ranking higher at in the EU-efficiency tables. These results are deviating from the actual energy yield measurements, which show a slightly different ranking. At one inverter, an accurate, but very slow MPPT algorithm that barely could follow quickly changing irradiance levels could be the reason for this effect. Another inverter switched off after operation at high power output for a while. Apparently, some inverters are been optimized to show excellent EU and CEC efficiency ratings. Two of the inverters featuring two inputs did not show an exceptional performance at the EU- and CEC-ratings, but they achieved top ranks at the AC energy yield for the first years. For the customer, the AC yield is a major performance indicator of any microinverter and should be included in the datasheet.
Keywords: yield; AC; micro-inverter; MPPT; CEC rating; EU efficiency; Photovoltaic; Solar

Meteorological Data Forecast using RNN - Balluff, Stefan; Bendfeld, Jörg; Krauter, Stefan (Deep Learning and Neural Networks)
Gathering knowledge not only of the current but also the upcoming wind speed is getting more and more important as the experience of operating and maintaining wind turbines is increasing. Not only with regards to operation and maintenance tasks such as gearbox and generator checks but moreover due to the fact that energy providers have to sell the right amount of their converted energy at the European energy markets, the knowledge of the wind and hence electrical power of the next day is of key importance. Selling more energy as has been offered is penalized as well as offering less energy as contractually promised. In addition to that the price per offered kWh decreases in case of a surplus of energy. Achieving a forecast there are various methods in computer science: fuzzy logic, linear prediction or neural networks. This paper presents current results of wind speed forecasts using recurrent neural networks (RNN) and the gradient descent method plus a backpropagation learning algorithm. Data used has been extracted from NASA's Modern Era-Retrospective analysis for Research and Applications (MERRA) which is calculated by a GEOS-5 Earth System Modeling and Data Assimilation system. The presented results show that wind speed data can be forecasted using historical data for training the RNN. Nevertheless, the current set up system lacks robustness and can be improved further with regards to accuracy.

Performance of MERRA2 Data Compared to Floating LiDAR - Bendfeld, Jörg; Balluff, Stefan; Wübbeke, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2017)

Short-term wind speed and power prediction for offshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krüger, J.; Krauter, Stefan (Proceedings of the DEWEK 2017)

Update on rankings of conversion efficiencies and energy yield of micro-inverters, including inverters for two PV modules - Bendfeld, Jörg; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017, S. 1477–1481)

Long-term performance of PV micro-inverters - Bendfeld, Jörg; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017, S. 1836–1840)

Introduction of an Advanced Method for Testing of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Testing and Analysis of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam, (Niederlande), 25.-29. Sept. 2017)

Offshore Metocean Station for Energy Purposes - Balluff, Stefan; Bendfeld, Jörg (Journal of Sustainable Development of Energy, Water and Environment Systems)

Einbindung von Oﬀshore Windenergie durch innovative Prognosemodelle und Speichertechnologien - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (14. Symposium Energieinnovation 2016)

Green Energy from the Ocean An overview on costeffectiv and reliable measuring systems - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Bestimmung der relevanten klimatologischen Parameter Oﬀshore - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Wissenschaftliche Verhandlungen 2016 der Deutschen Physikalischen Gesellschaft Regensburg)

Systemvergleich zur zeitlich und örtlich hochaufgelösten Einstrahlungsmessung - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Wissenschaftliche Verhandlungen 2016 der Deutschen Physikalischen Gesellschaft Regensburg)

Deviations of results for energy yield from efficiency rankings of micro-inverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 31st European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 20.–24. Juni 2016, S. 1508–1511)

Short term wind and energy prediction for offshore wind farms using neural networks - Balluff, Stefan; Bendfeld, Jörg; Krauter, Stefan (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources and the use of hydro power for fluctuation compensation in Cameroon - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Cost, performance, and yield comparison of eight different micro-inverters - Krauter, Stefan; Bendfeld, Jörg (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Stabilizing oﬀshore wind farm power feed-in via power to gas storage systems - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Discovering the potential for oﬀshore windfarms trough measurements - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Wind power forecasting for oﬀshore wind farms - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore wind energy development based on Merra data - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore metocean station for energy purposes - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Short term wind and energy prediction for oﬀshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (EWEA Forecasting 2015 Technology Workshop)

Integration of Wind Energy in Power System—Modelling of a Market Oriented Energy Concept - Bouyraaman, Yassin; Bendfeld, Jörg; Breymann, Philipp; Krauter, Stefan (Renewable Energy in the Service of Mankind Vol I)

Integration of offshore wind energy into the grid system in Germany: Modelling of a market oriented energy provision - Bouyraaman, Yassin; Bendfeld, Jörg; Krauter, Stefan (14th IAEE European Energy Conference- Sustainable Energy Policy and Strategies in Europe, Rome, Italy, October 28-31, 2014)

Integration of wind energy in power systems: Modeling of a market-orientated energy concept - Bouyraaman, Yassin; Bendfeld, Jörg; Krauter, Stefan; Breymann, P. (Proceedings of the World Renewable Energy Congress WREC XIII, London, (UK), August 3-8, 2014)

Reduction of Offshore Wind farm power Feed-in ﬂuctuations via Power to Gas Storage Systems - Bouyraaman, Yassin; Bendfeld, Jörg (Solar 2014/Intersolar North America, San Francisco, July 6-10, 2014)

Advanced offshore Measurements for Windfarms - Bendfeld, Jörg; Balluff, Stefan (Solar 2014/Intersolar North America, San Francisco, July 6-10, 2014)

Performance and Yield Comparison of seven different Micro-Inverters. - Krauter, Stefan; Bendfeld, Jörg; Gohardehi, A.; Sadati, A. (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Micro combined heat and power plants (micro-CHP) in combination with photovoltaics for autonomous local power and heat supply. - Krauter, Stefan; Bouyraaman, Yassin; Bendfeld, Jörg; Japs, Ewald (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Foundation Monitoring – An Overview of Methods and Measurement Solutions - Bendfeld, Jörg; Krieger, Jens (WINDFORCE 2013 Bremerhaven, 9. WAB Offshore-Windenergie Konferenz, Juni 2013)

7 YEARS METEOMAST AMRUMBANK WEST - Bendfeld, Jörg; Krieger, Jens (Europe’s Premier Wind Energy Event – EWEA 2013 Annual Event, Vienna, Austria, February 2013)

FOG MEASURING AND SELECTED OFFSHORE FOG OCCURRENCES FOR THE OFFSHORE WIND ENERGY - Bendfeld, Jörg; Balluff, Stefan; Bouyraaman, Yassin; Krieger, jens (Europe’s Premier Wind Energy Event – EWEA 2013 Annual Event, Vienna, Austria, February 2013)

FOUNDATION MONITORING FOR OFFSHORE WINDFARMS - Krieger, Jens; Bendfeld, Jörg (Europe’s Premier Wind Energy Event – EWEA 2013 Annual Event, Vienna, Austria, February 2013)

Optimisation of Offshore Wind farm Feed-in fluctuations via Power to Gas Storage Systems - Bouyraaman, Yassin; Bendfeld, Jörg (Europe’s Premier Wind Energy Event – EWEA 2013 Annual Event, Vienna, Austria, February 2013)

Measurements for PV-Module outdoor performance - Bendfeld, Jörg (Wissenschaftliche Verhandlungen 2013 der Deutschen Physikalischen Gesellschaft)

Foundation monitoring for offshore windfarms - Krieger, Jens; Bendfeld, Jörg (Wissenschaftliche Verhandlungen 2013 der Deutschen Physikalischen Gesellschaft)